A comparison of mass parameters determination using capacitive and optical sensors - Carvalho, Vítor (2011)
This paper presents a comparison study between the use of 1mmresolution capacitive and optical sensors for the determination of yarn mass parameters. A parallel plate capacitive sensor to determine yarn mass variations and a yarn diameter and hairiness determination solution using optical sensors and integrating optical signal processing based on Fourier analysis are described. As there is a high correlation between yarn diameter and yarn mass, it is possible to determine yarn mass and infer variations in yarn diameter and vice versa. Moreover, by optically detecting the degree of yarn hairiness, one can quantify its influence on the capacitive sensor mass variation measurements. Here we present the results of a signal processing analysis and statistical description of measurements carried out in two 100% cotton yarns with a linear mass of 59 and 295 g/km performed in yarn system quality (YSQ) machine. We conclude that an accurate yarn characterization can be carried out using optical sensors alone, reducing system’s cost and complexity and increasing efficiency.